PD-1 suppresses human CD38+ circulating Tfr cells and regulates humoral immunity - Heng Zhang; Hui Zheng; Lin Guo; Ying Tong; Xiaolu Ma; Yanchun Wang; Renquan Lu; Cuncun Chen; Suhong Xie (Journal for ImmunoTherapy of Cancer)
Background Anti-programmed cell death protein 1 (anti-PD-1) antibodies have achieved revolutionary success in cancer therapy. However, the impact of anti-PD-1 therapy on host humoral immunity in humans during cancer immunotherapy requires further investigation.Methods We evaluated immunoglobulin titers by ELISA and screened the immune landscape of immune cells from 25 healthy donors and 50 cases including 25 new-onset hepatocellular carcinoma (HCC) patients prior to systemic treatment and 25 HCC patients undergoing anti-PD-1 therapy by multicolor flow cytometry. Flow or beads sorted cells were cultured ex vivo for proliferation and functional analysis.Results Anti-PD-1 therapy significantly increased the levels of IgG and IgA in the periphery of HCC patients. Anti-PD-1 treatment led to an increase in plasmablasts and a notable rise in circulating T follicular regulatory (cTfr) cells, while changes in circulating B cells, T follicular helper cells, or regulatory T cells were not significant. Anti-PD-1 therapy also influenced the proliferation and function of cTfr cells, promoting the differentiation of CD38+ cTfr cells. We observed that the CD38+ Tfr cell subset in the peripheral blood can promote plasmablast differentiation, associated with altered antibody production.Conclusions Together, these data demonstrate the immunomodulatory role of PD-1 in restricting the differentiation and function of human cTfr cells and in regulating humoral immunity.